Technologies Solutions Schemes for Patients’ Rehabilitation - Fardoun, Habib M.; Mashat, Abdulfattah S. (Methods of Information in Medicine, 2017)
Objective: The present editorial is part of the focus theme of Methods of Information in Medicine entitled “Technologies solutions schemes for Patients’ Rehabilitation: Methodologies, Models and Algorithms”. The focus theme aims to present nowadays most innovative solutions to improve patients’ rehabilitation by applying and using sophisticated and pioneering Information and Communication Technologies (ICT) and human factors.Methods: The focus theme explores the different existent research works and tools used, applied and developed for incapable people in terms of rehabilitation and health care, as to look into the extent methodologies, models and algorithms by means of ICT in this process.Results: The focus theme lists a group of research works, which are presenting various solutions using ICT systems to improve the rehabilitation process of people with physical incapacities and to help them in carrying out their daily life.
Keywords: Training tools for rehabilitation; virtual rehabilitation; rhythmic rehabilitation; gait rehabilitation; rehabilitation robotics; multi-user systems for user interaction; virtual humans; communications aids